The Effectiveness of Storytelling Method in Enhancing Oral Health Knowledge Among Early Childhood - Suci Suci Rahmasari; Yona Ladyventini; Rahmi Khairan (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
Dental caries remains a major oral health problem among children and highlights the need for effective oral health education from an early age. This study aimed to evaluate the effectiveness of the storytelling method compared with traditional lecture-based education in improving oral health knowledge among children. A quasi-experimental study with a pre-test and post-test control group design was conducted among 108 children aged 7–8 years at the Dental and Oral Hospital of Andalas University, Indonesia. Participants were divided into a storytelling group (n = 54) and a lecture group (n = 54). The storytelling group received three oral health education sessions using illustrated stories, while the lecture group received the same material through conventional lectures. Data were analyzed using the Shapiro–Wilk normality test, paired sample t-test, independent t-test, and Chi-square test. The results showed that the proportion of children with good knowledge was higher in the storytelling group (83.3%) than in the lecture group (51.9%), with no children in the storytelling group categorized as having poor knowledge. The storytelling group also had a higher post-test mean score (8.39 ± 1.04) than the lecture group (7.20 ± 1.77), and the educational method was significantly associated with knowledge level (p = 0.001). In conclusion, storytelling is more effective than traditional lectures in improving children’s oral health knowledge. Keyword : storytelling; oral health education; dental caries; children; knowledge